Effectiveness of Influenza Vaccine in Hemodialyzed Patients: A Retrospective Study. Issue 1 (19th August 2018) - Cohen‐Hagai, Keren; Kotliroff, Andy; Rozenberg, Ilan; Korzets, Zeev; Zitman‐Gal, Tali; Benchetrit, Sydney
Abstract: Infection is one of the leading causes of mortality in dialysis patients, second only to cardiovascular disease. This retrospective study assessed the efficacy and clinical outcomes of influenza vaccination among hemodialysis (HD) patients. In the 2014–2015 season, 104 of 164 (63.6%) HD patients were vaccinated for influenza by the outpatient community health system facilities. Significantly more patients, 159 of 170 (93.8%), were vaccinated in 2015–2016 by the hospital dialysis unit staff during an inpatient HD session ( P <0.001). A trend toward fewer complications from influenza infection was observed in vaccinated patients. Among HD patients with diabetes (who comprised 56% of the study population), the incidence of influenza was 17% among nonvaccinated patients vs. 6.3% among those who were vaccinated ( P =0.026). The inpatient vaccination policy resulted in a greater rate of vaccination. HD patients with diabetes benefit from influenza vaccination, with a significantly lower incidence of influenza infection.